KOORDINASI DINAS PERHUBUNGAN SATUAN LALU LINTAS KEPOLISIAN RESOR KOTA BESAR (SATLANTAS POLRESTABES) DALAM PENERTIBAN PARKIR LIAR DI JALAN SUTOMO MEDAN - Agnes Maria Sabrina Sinaga; Februati Trimurni (Smart Education, 2023)
he rise of existing illegal parking can interfere with the mobility of road users in carrying out their activities. In this case, the coordination of illegal parking control is carried out by the Departement of Transportation and Satlantas Polrestabes Medan. The obstacles in controlling illegal parking on Jalan Sutomo are the lack of unification of action between stakeholders, namely controls that are not routinely carried out, the communication that is established is still waiting for news, the action against traffic violators is also still minimal and also the level of compliance with existing regulations, resulting in illegal parking still developing today.The findings applied qualitative methods, which were analyzed descriptively. Data collection techniques were carried out by means of interview, observation and documentation. Before going to the field, the researcher firstly prepared and used interview, observation and documentation guidelines.The findings are, Coordination of the Departement of Transportation and in accordance with the Hasibuan indicator, namely the unity of communication actions, division of labor and discipline. The unit of actions carried out based on the Mayors regulation number 70 of 2017 concerning procedures for moving/craning, towing locks and blowing out the wheel. The communication, Departement of Transportation and Satlantas Polrestabes Medan communicated verbally and in writing viaWhatsApp, e-mail, and letters sent by the executor of illegal parking control activities. The division of labor was carried out based on government regulation number 80 of 2012 concerning procedures of inspection of motorized vehicles on the road and prosecution of traffic and transportation violations. The discipline carried out by the Departement of Transportation and Satlantas Polrestabes Medan is the compliance of both institutes regarding regulation compliance with the directions given.